Research on the online temperature measuring device in outdoor high-voltage isolation Switch. Issue 1 (January 2020) - Hu, Ran; Du, Xuecheng; Hu, Guojun; Hong, Meng; Jiang, Rufeng; Wei, Tengfei; Deng, Erhong; Li, Yongjian
Abstract: In view of the frequent overheat or even fusion accidents of outdoor high-voltage isolation switch contacts in operation, and they are serious threats to its equipment security and the reliability of power network. To mitigate and reduce the influence effected by abnormal heat of isolating switch contacts, this paper describes the structure of the temperature measuring device, the temperature chip, the wireless communication mode. Moreover, the on-line temperature measuring device's characteristic of structure and function was summarized. The experimental dada shows that the device has large measuring range, high precision, high reliability and availability. In order to understand the operation status of outdoor high-voltage isolators, the device can realize real-time measurement the temperature without the technical personnel at the scene.